THE IMPLEMENTATION INTERNAL CONTROL OF ACCOUNT RECEIVABLE IN KUD TANI WILIS SENDANG TULUNGAGUNG - Annisaa Miftahul Ni'mah; Novi Khoiriawati (BALANCE: JOURNAL OF ISLAMIC ACCOUNTING, 2022)
The background to this research is that the KUD Tani Wilis Sendang Savings and Credit Unit is one of the cooperatives that provide debt and credit services to help the economy of the surrounding community. In its operational activities, the Savings and Credit Unit of Tani Wilis has an internal control of receivables which is a process or a plan implemented by the management to support the success of the company. Internal control is very important, where if one of its components is not respected, there will be a synchrony between the objectives of the company and the reality. The objectives of this study are (1) to assess the application of internal control of receivables based on the COSO framework, (2) to describe the obstacles to the implementation of internal control of receivables in the Savings and Credit Unit by KUD Tani Wilis Sendang, and (3) describe solutions to overcome obstacles to the implementation of internal control over receivables. The method of this study uses a qualitative approach. The data sources obtained are primary and secondary data. Data were collected through interviews, observations and questionnaires. The data analysis technique used is triangulation. The results showed that (1) the implementation of internal control of receivables at the KUD Tani Wilis Sendang Credit and Savings Unit had been implemented with a score of 70.8%. (2) The obstacles encountered by the Savings and Loans Unit of KUD Tani Wilis Sendang are non-performing debts caused by customers who do not want to pay their debts. (3) The solutions given to overcome the obstacles are customer analysis and the imposition of fines and forfeiture of collateral. The results of this study are expected to provide information and input to KUD Savings and Credit Unit Tani Wilis Sendang to optimize the implementation of internal debt control